CHARACTERIZATION OF CD68 + AND CD163 + INFILTRATION BY PRIMARY FOCUS MACROPHAGES AND METASTATIC LESIONS OF REGIONAL LYMPH NODES IN LUMINAL INVASIVE BREAST CARCINOMAS, DEPENDING ON THEIR IMMUNOPHENOTYPE - Aykian, A.Z.; Shynkevych, V.I.; Kaydashev, I.P. (World of Medicine and Biology, 2018)
M1 Tumor-associated macrophages (TAM) have an important antitumor activity that can eliminate cancerous cells by producing compounds and isolate chemokines that recruit and reward T-cells of the antitumor phenotype, which leads to the tumor growth retardation or regression. M2-like TAMs, on the other hand, can actively contribute to each stage of the tumor development and progression. The peculiarities of TAM localization in the departments of the dreast gland cancer (BGC), and their density are related to immunohistochemical characteristics of tumors, their malignant phenotype and prognosis. The study of the correlations between pathohistological, IHC characteristics of BGC, and the representation of TAMs in them is important for understanding the possible local functions and their consequences. In our study, quantitative characteristics and features of CD68 + and CD163 + M2-like PAMs localization, which infiltrate the histochemical subtypes of luminal carcinomas (luminal A, luminal HER2-negative, and luminal B HER2-enriched), in the primary focus without metastases and in matched samples are presented. with metastases into the lymph nodes in connection with the morphological and immunophenotypic BGC characteristics, for studying their diagnostic and pathogenetic role. The research material was represented by intraoperative tissues of tumors and ipsilateral lymph nodes obtained at radical removing of mammary glands. The mean age of patients was 58 years, ranging from 30 to 79. Immunohistochemical characteristics of the removed tumors (HER2, ER, PR, Ki67) were used to select a group of luminal samples. The biopsy material was divided into three groups according to clinical IHC-characteristics: the first one - luminal A, the second - luminal B HER2-negative, the third - luminal B HER2-enriched; with two subgroups in each group: N0 and N1, with 3 biopsies in each one. The total of 18 samples were under study. The assessment of immunohistochemical coloring was performed by counting CD68 + TAM and CD163 + M2-like TAMs under a light microscope in at least 5 fields of view of the intensive IHC-reaction in each section, calculating the arithmetic mean, within the tumor nests and stroma. The count included immunopositive cells with macrophage morphology. The study is organized as a pilot project to test the hypothesis about the TAM features according to the BGC varieties. Luminal A (ER + / HER2-) is the most common luminal subtype. CD68 + PAM were located in different ways, but in the stroma their presence was more regular than in tumor nests. CD163 + M2-like cells did not accurately repeat the localization of the total macrophages fraction, coinciding in the peripheral fat and desmoplastic parts of the stroma and in certain nests (in smaller numbers), and forming the second line of infiltration in the stroma, at a distance from the nests. When comparing the luminal A subgroups based on N0 / N1, no sharp differences were noted, although the number of M2 with N0 was slightly higher, compared to N1, however, it did not reach statistical significance. Regarding luminal В HER2-negative subtype, with CD68 + TAM an even and uneven distribution was reported, with presence in the stroma and in the nests. There was very little CD163 + M2 in all samples, and co-localization with TAM was observed in the stroma, in the necrosis zone and, individually, in the nests. In luminal B HER2-enriched, CD68 + TAM, not at a high level, but regularly, were present in all tumor departments, although unevenly due to the low infiltration rate in all samples. CD163 + M2 is slightly increased in the number with metastases (0-1 at N0, and 3.4, 1.7; 3 - at N1); were only locatedas foci in the stroma and necrotized areas, where their number often practically coincided with CD68 + TAM (may be, these areas were infiltrated with M2 exclusively). In the nests, CD163+М2 were single or missing. Conclusions 1. Positive ER-status of the luminal BGC studied samples may be due to a relatively lower level of their TAM infiltration. 2. Typical localization of CD68 + TAM in luminal BGC samples was detected: in the stroma, tumor nests, and / or around necrosis areas; with the formation of aggregations and / or clusters. A certain area of tumor complexes not involved by TAM was regularly observed. The CD163 + M2 co-localization was observed in the peripheral fatty and desmoplastic tumor stroma divisions as well as in certain nests (in smaller numbers). 4. A reliable feedback was revealed between the G-degree of luminal BGC and the level of CD68 + PAM infiltration.